Inhibition of demand pacemakers caused by potentials associated with inspiration. Issue 2 (February 1976) - Peter, T; Harper, R; Sloman, G
Abstract : A 69-year-old man with a permanent demand pacemaker and a unipolar electrode system had intermittent failure of pacing during deep inspiration. Pacing was not interrupted when the unit was switched to fixed rate mode by an external magnet. Thus, the problem was not caused by a change in electrode position or to a loose connexion. The likely cause was inhibition by non-cardiac potentials, possibly myopotentials associated with respiration.